Determination of Folic Acid in both Pure and Pharmaceutical Preparations via Oxidative Coupling Reaction - Sager, Athra G.; Katoof, Zeena R.; Radh, Rusul S. (Iraqi Journal of Science, 2023)
In this study, the development of an indirect spectrophotometric method for the determination of folic acid in pure and pharmaceutical preparations is described. The method is based on the oxidation of pyrocatechol with iron (III) in an acidic medium, followed by the reaction with folic acid (FA) to produce a stable, water-soluble orange compound with maximum absorption at 350 nm versus the blank reagent. The complex of charge transfer was studied under optimal conditions; the titration graph was linear over the range of 0.5-25 μg/mL with a relative error of 1.2-2.8 and a relative standard deviation of 2.43-1.45 depending on the concentration level.